2007
DOI: 10.1158/0008-5472.can-06-2583
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Induced Oxidative Stress Perturbs Nuclear Factor-κB Activity-Augmenting Tumor Necrosis Factor-α–Mediated T-Cell Death: Protection by Curcumin

Abstract: Cancer patients often exhibit loss of proper cell-mediated immunity and reduced effector T-cell population in the circulation. Thymus is a major site of T-cell maturation, and tumors induce thymic atrophy to evade cellular immune response. Here, we report severe thymic hypocellularity along with decreased thymic integrity in tumor bearer. In an effort to delineate the mechanisms behind such thymic atrophy, we observed that tumor-induced oxidative stress played a critical role, as it perturbed nuclear factor-KB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 50 publications
3
92
0
1
Order By: Relevance
“…Previously, we have shown that curcumin can induce tumor-cell killing, lower systemic toxicity and neutralize oxidative stress in the immune system, resulting in Tcell protection. [28][29][30] Here we report that curcumin reduced the levels of TGF-b and IL-10 in Treg cells and reduced the number of Treg cells in the tumor-bearing hosts. Complex interactions between various signals produced by the tumor and by curcumin ultimately result in augmentation of Th1/Tc1-type responses in the tumor-bearing host.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previously, we have shown that curcumin can induce tumor-cell killing, lower systemic toxicity and neutralize oxidative stress in the immune system, resulting in Tcell protection. [28][29][30] Here we report that curcumin reduced the levels of TGF-b and IL-10 in Treg cells and reduced the number of Treg cells in the tumor-bearing hosts. Complex interactions between various signals produced by the tumor and by curcumin ultimately result in augmentation of Th1/Tc1-type responses in the tumor-bearing host.…”
Section: Discussionmentioning
confidence: 68%
“…We recently demonstrated that curcumin reduced the overall systemic toxicity, while effectively lowering the tumor burden, and prevented tumor-induced T-cell depletion. [28][29][30] This is the first time we are reporting the intricate mechanism of curcumin-induced immune restoration in tumor-bearing animals, and our results suggest that curcumin can prevent tumorinduced immunosuppression via restoration of effector T-cell populations, normalization of the cytokine profile and downregulation of Treg cell activity.…”
Section: Cd8mentioning
confidence: 60%
See 1 more Smart Citation
“…Similarly, curcumin has shown numerous therapeutic characteristics (Srivastava et al 2011). This chemical improves the immune reconstitution during carcinogenesis (Bhattacharyya et al 2007(Bhattacharyya et al , 2010 and prevents deltamethrin-induced thymocyte apoptosis by arresting the oxidative stress through caspasedependent signaling pathways (Kumar et al 2015). Fibroblast growth factor 21 (FGF21) plays a critical role in the regulation of energy metabolism (Salminen et al 2016) and protects against age-associated thymic involution by increasing the cortical TEC and thymocyte progenitors in mice (Youm et al 2016).…”
Section: Can Ati Be Reversed Therapeutically?mentioning
confidence: 99%
“…Curcumin is the main component of turmeric. Studies have found that curcumin can inhibit tumor growth by inhibiting angiogenesis both in vivo and in vitro (11)(12)(13)(14)(15). However, the development of endometriosis and the impact of angiogenesis is rarely reported.…”
Section: Introductionmentioning
confidence: 99%